A review of wave energy technology from a research and commercial perspective. Issue 14 (5th October 2021) - Guo, Bingyong; Ringwood, John V.
Abstract: Although wave energy prototypes have been proposed for more than 100 years, they have still not reached full commercialisation. The reasons for this are varied, but include the diversity of device operating principles, the variety of onshore/nearshore/offshore deployment possibilities, the diversity of the wave climate at various potential wave energy sites, and the consequent lack of convergence in technology and consensus. This distributed effort has, in turn, lead to a slow rate of progression up the learning curve, with a significant number of wave energy company liquidations and technical setbacks dampening investor confidence. Although a number of reviews on wave energy technology are already in the published literature, such a dynamic environment merits an up‐to‐date analysis and this review examines the wave energy landscape from a technological, research and commercial perspective.